KEMISKINAN DI PERMUKIMAN PADAT PENDUDUK JOHAR BARU JAKARTA DALAM KARYA SENI POP-UP - Efendi, Irfan; Moerdisuroso, Indro (Qualia: Jurnal Ilmiah Edukasi Seni Rupa dan Budaya Visual, 2024)
Poverty is a condition of economic inability to meet the average standard of living. In every urban area there are several densely populated settlements that are slum and uninhabitable, one of which is Johar Baru Jakarta. The creation of this work aims to reflect poverty in the densely populated settlement of Johar Baru Jakarta through pop-up artwork. This study uses a qualitative method with an artistic research approach. The creation of the work uses semi-figurative form interests, reflective art interests, and postmodern aesthetic principles. The specialness of personal style can be seen from the visual lining technique with the characteristics of thick and thin lines. The creation of this work is expected to be knowledge to the wider community about life in densely populated settlements.